Molecular understanding of the LCST phase behaviour of P(MEO2MA-b-OEGMA) block copolymers. Issue 4 (4th March 2021) - Ye, Zhicheng; Su, Haiping; Lian, Cheng; Hu, Jiajie; Shang, Yazhuo; Liu, Honglai
ABSTRACT: The lower critical solution temperature (LCST) behaviour of block copolymer 2-(2-methoxyethoxy) ethyl methacrylate and oligo (ethylene glycol) methacrylate (P(MEO2 MA-b-OEGMA)) was studied by molecular dynamics simulations. Our simulations show that the LCST of P(MEO2 MA-b-OEGMA) is linear to its OEGMA block ratio, which is agreed with our previous experimental observations. Meanwhile, the mechanism of the LCST phase behaviour was also revealed by our simulations. The hydrophilic effect of copolymer and the entropy effect of water are the main factors of affecting the aggregate behaviours of copolymers and further affect their LCSTs. The hydrophilic effect is dominant and these water molecules are apt to gather around the copolymers and the copolymers exist in a coil state when the temperature is relatively lower. However, the entropy effect of water prevails and the copolymers tend to in a globule state when the temperature is higher. The coil-to-globule transition occurs when the temperature reaches a certain degree, namely LCST, at which the competition between the hydrophilic effect of copolymer and entropy effect of water reaches a balance.